2002
DOI: 10.1074/jbc.m205264200
|View full text |Cite
|
Sign up to set email alerts
|

Direct in Vivo Screening of Intrabody Libraries Constructed on a Highly Stable Single-chain Framework

Abstract: Single-chain Fv antibody fragments (scFv) represent a convenient antibody format for intracellular expression in eukaryotic or prokaryotic cells. These so-called intrabodies have great potential in functional genomics as a tool to study the function of newly identified proteins in vivo, for example by binding-induced modulation of their activity or by blocking interactions with other proteins. However, the intracellular expression and activity of many single-chain Fvs are limited by their instability and foldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 49 publications
(81 reference statements)
1
24
0
Order By: Relevance
“…Thus, we used a yeast two-hybrid approach to select scFvs that recognize this LBD epitope and hypothesized that such scFvs may show inhibitory effects on the ligand/receptor interaction. scFvs were initially selected from a library of randomized complementarity-determining region 3 (CDR-3) of the heavy chain (Auf der Maur et al , 2002). The library was constructed within an scFv framework (FW) (Auf der Maur et al , 2004) that served as the negative control in the experiments reported here.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we used a yeast two-hybrid approach to select scFvs that recognize this LBD epitope and hypothesized that such scFvs may show inhibitory effects on the ligand/receptor interaction. scFvs were initially selected from a library of randomized complementarity-determining region 3 (CDR-3) of the heavy chain (Auf der Maur et al , 2002). The library was constructed within an scFv framework (FW) (Auf der Maur et al , 2004) that served as the negative control in the experiments reported here.…”
Section: Resultsmentioning
confidence: 99%
“…We thus applied our yeast two-hybrid, antigen–antibody interaction screening technology to isolate antigen-binding scFvs by screening a human scFv library of randomized synthetic CDR-H3 sequences (Auf der Maur et al , 2002). The library was constructed on an scFv-FW that had been previously isolated by a yeast screening system (Auf der Maur et al , 2001, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, specific Abs were obtained from libraries with introduced diversity only to CDRH3. [28][29][30] However, the relative importance of CDRH3 compared to other CDRs has been recently revisited in numerous studies. Large scale analyses 39,46 of Abs have assessed the role of CDRH3.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] In addition, many synthetic libraries are based on a single, [24][25][26] or limited set of V region frameworks 17,27 and many introduce diversification only to CDRH3. [28][29][30] Similarly, some libraries limit the introduced diversity to only 2-4 amino acids per position. 31,32 A critical question, therefore, in designing synthetic libraries is to what extent the resulting Abs are similar to natural Abs in the way they recognize and bind the Ag.…”
Section: Introductionmentioning
confidence: 99%